Distribution of Biominerals and Mineral-Organic Composites in Plant Trichomes - Ensikat, Hans-Jürgen; Weigend, Maximilian (Frontiers in Bioengineering and Biotechnology, 2021)
Biomineralization is a common phenomenon in plants and has been shown to be chemically, functionally and topologically diverse. Silica and calcium carbonate have long been known as structural plant biominerals and calcium phosphate (apatite) – long known from animals – has recently been reported. Strikingly, up to three different biominerals may occur in a single trichome in, e.g., Urticaceae and Loasaceae, and in combination with organic compounds, can form organic/inorganic composite materials. This article presents an extension of previous studies on the distribution of these biominerals in Loasaceae trichomes with a focus on their spatial (three-dimensional) distribution and co-localization with organic substances. Light microscopy and scanning electron microscopy with high-resolution EDX element analyses of sample surfaces and sections illustrate the differential distribution and composition of the different biomineral phases across cell surfaces and cell walls. Raman spectroscopy additionally permits the identification of organic and inorganic compounds side by side. All three biominerals may be found in a nearly pure inorganic phase, e.g., on the plant surfaces and in the barbs of the glochidiate trichomes, or in combination with a larger proportion of organic compounds (cellulose, pectin). The cell lumen may be additionally filled with amorphous mineral deposits. Water-solubility of the mineral fractions differs considerably. Plant trichomes provide an exciting model system for biomineralization and enable the in-vivo study of the formation of complex composite materials with different biomineral and organic compounds involved.